ผลของรังสีแกมมาแบบเฉียบพลันต่อการเปลี่ยนแปลงลักษณะสัณฐานของต้นแววมยุราพันธุ์พื้นเมือง - อินทนนท์, อำพรรณ; เตชีศีลพิทักษ์, ธัญญะ; จาละ, อัญชลี; จันจุฬา, ณัฐพงค์; บาลลา, นุชรัฐ (Thai Journal of Science and Technology, 2018)
Abstract The effect of acute gamma irradiation on morphological changes in native Torenia (Torenia fournieri) was studied by using leaves which were irradiated with gamma rays at the doses of 0, 20, 40, 60, 80, and 100 grays. After 60 days of leaf cuttings, survival rate was recorded. It was found that by increasing dosage of gamma radiation, survival rate was decreased. The relationship between concentration of gamma radiation and survival percentage was graphed to get LD50(60). It was found that 51 grays radiation resulted in 50 percent survival after 60 days. The number of new shoots from 60, 80 and 100 gray leaves were less than that of the control. However, it is observed that the number of new shoots was highest at 20 grays (5 shoots). When new shoots were 120 days after radiation treatment, the height and the canopy width were lower in the groups exposed to gamma radiation at 80 and 100 grays. As for morphological changes after irradiation, some specimens in the 40 grays treatment group had short leaves, round serrate and dentate leaves. The guard cells and subsidiary cells were abnormal and numbers of abnormal guard cells were increased when dosage of gamma radiation increased. Keywords: survival rate; acute gamma irradiation; guard cell; leaf cutting